Snail and Axin2 expression predict the malignant transformation of oral leukoplakia. (October 2017) - Zhang, Xianglan; Kim, Ki-Yeol; Zheng, Zhenlong; Kim, Hyun Sil; Cha, In Ho; Yook, Jong In
Highlights: Snail and Axin2 are useful biomarker(s) of malignant conversion in oral leukoplakia. Constructed a nomogram for prediction of malignant conversion of oral leukoplakia. Snail, Axin2, and clinical factors were included in the predictive nomogram. The nomogram showed high levels of prediction probability. Abstract: Objectives: Oral leukoplakia (OL) has a well-documented potential risk of malignant transformation into oral squamous cell carcinoma (OSCC), although biomarker(s) predicting malignant potential are limited in capability. The aim of this cross-sectional and retrospective cohort study was to investigate the predictive role of canonical Wnt genes Axin2 and Snail ( SNAI1 ) expression in the malignant transformation of OL lesions. Materials and methods: The expression of epithelial-mesenchymal transition (EMT) genes Snail and Axin2, which are regulated by the canonical Wnt pathway, were determined using immunohistochemical staining in an OL cohort consisting of 154 samples of patients with long-term follow-up and then evaluated as risk factors for malignant transformation of OL. Results: Increased Axin2 and Snail abundance were found in 107 (69.5%) and 58 (37.7%) of OL patients, respectively. In a multivariate analysis using gender, age, lesion site, Axin2, and Snail as cofactors, both Axin2 and Snail were independent risk factors for malignant transformation with a hazard ratio of 7.47 (95% confidence interval, 2.23–25.02; P = 0.001) and 4.41 (95% confidence interval, 1.78–10.93; P = 0.001), respectively. A nomogram for predicting 5-, 10-, and 15-year cancer-free survival probability was developed in patients with OL by including gender, age, lesion site, Axin2, and Snail expression with a c-index of 0.760. Conclusion: The increased abundance of Snail and Axin2 is highly correlated to malignant transformation of OL, making them novel biomarker(s) predicting oral cancer development.